2018
DOI: 10.25077/jka.v7i0.872
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Dadih dengan Perubahan Jumlah Lactobacillus fermentum Pada Feses Ibu Hamil

Abstract: AbstrakIbu hamil dengan asupan probiotik yang baik diketahui memiliki fungsi imun yang lebih baik dan kehamilan yang lebih sehat, menekan angka kejadian bayi prematur serta menurunkan prevalensi preeklamsi. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian dadih terhadap jumlah L. fermentum pada feses ibu hamil. Penelitian ini dilakukan dengan desain equivalent pre-post test with control group. Populasi penelitian ini adalah ibu hamil dan sampel penelitian dipilih secara konsekutif. Setelah melakuka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The mechanism of action behind the health benefits is largely unknown, but several probiotic strains have been isolated from dadih, which may contribute to its health properties (Venema & Surono, 2018). Several studies had demonstrated that Dadih has beneficial effects on the intestinal health of mothers and children due to its nutritional value and its role as a probiotic (Balqis et al, 2018). For pregnant women, it can lower the abortus rate and can increase immunity during pregnancy (Purwati, 2018).…”
Section: The Effect Of Additional Dadih On Lactic Acid Bacteria and N...mentioning
confidence: 99%
“…The mechanism of action behind the health benefits is largely unknown, but several probiotic strains have been isolated from dadih, which may contribute to its health properties (Venema & Surono, 2018). Several studies had demonstrated that Dadih has beneficial effects on the intestinal health of mothers and children due to its nutritional value and its role as a probiotic (Balqis et al, 2018). For pregnant women, it can lower the abortus rate and can increase immunity during pregnancy (Purwati, 2018).…”
Section: The Effect Of Additional Dadih On Lactic Acid Bacteria and N...mentioning
confidence: 99%
“…There are no pathogenic bacteria in Dadiah [19]. Several studies had demonstrated that Dadiah had beneficial effects on the intestinal health of mothers and children due to its nutritional value and its role as a probiotic [19], [20], [21], [22], [23], [24]. Dadiah had more calories than yogurt from cow's milk [19].…”
Section: Introductionmentioning
confidence: 99%